Design of a multi-bit quantization high-precision microaccelerometer system - Wang Baosheng; Zhao Gangbin (Dianzi Jishu Yingyong, 2018)
In order to achieve a stable and high-precision micromechanical accelerometer system based on the system noise-shaping ability, a high precision accelerometer system with multi-bit quantization is proposed. A fourth-order multi-bit quantized micromechanical accelerometer topology is realized by applying an electrostatic feedback linearization circuit. The average noise level of the accelerometer system is lower than -120 dB/√Hz. The sensitivity and the equivalent input acceleration noise are about 0.63 V/g and 4 μg/√Hz, respectively. The input range of the accelerometer system is about ±3 g, which is limited by the supply voltage and system sensitivity.